Enhancement of Ge-based p-channel vertical FET performance by channel engineering using planar doping and a Ge/Si x Ge1-x-ySn y heterostructure model for low power FET applications - Elogail, Yasmine; Fischer, Inga A.; Wendav, Torsten; Schulze, Jörg (Semiconductor Science and Technology, 2018)
High mobility materials are being studied to replace Si with the aim of enhancing the performance of nanoelectronic devices. Ge and III-V channels have recently received a lot of attention, where the combination of III-V channels in n-MOSFETs and Ge channels in p-MOSFETs integrated on Si substrates is regarded as a promising CMOS design. Ge integrated on Si is a very promising choice due to its superior transport properties and compatibility to CMOS technology. The main challenges faced by Ge-based FETs are the channel/gate interface quality, crystal defects due to integration on Si and the smaller bandgap compared to Si, which leads to elevated band-to-band-tunnelling leakage currents, setting limitations on the achievable off state current (I OFF). In this work, we present results on the fabrication and characterization of vertical Ge-based p-channel planar doped barrier FET together with a simulation model based on extracted material data from our experimental work and literature. Based on the model, a design of a modified device using both planar doping and a heterostructure in the channel is presented. The channel engineered design uses a Ge/Si x Ge1-x-ySn y heterostructure, which is lattice matched to Ge, within the channel at different positions. The results show improved performance; the larger bandgap of the ternary alloy Si x Ge1-x-ySn y compared to Ge leads to a suppression of the I OFF as well as a reduced subthreshold swing, making the heterostructure device promising for energy efficient FET applications.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Ge nano-FETs; heterostructure channel engineering; low power FET; planar doped barrier FETs; SiGeSn heterostructure